(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This article focuses on the Economic Theory of the Health Market, based on the contributions generated by David Ricardo's Economic Theory, commonly known as Ricardian Theory, which for this article will be referred to as Ricardian Economics (RE). Methodologically, documentary research was carried out, using Google Scholar, open websites and academic institutions, based on the search for keywords such as Ricardian theory, health market. It was also possible to visit articles and dissertations, which allowed us to verify that RE cannot find a standard capable of measuring the value of all things [a fact that can be inferred in the analysis of the health market, through health economics] and that the market has its specificities to respect in order to implement a particular economic policy.